Leaf size and thickness are related to frost damage in ground layer species of Neotropical savannas - de Antonio, Ariadne Cristina [UNESP]; Scalon, Marina Corrêa; Rossatto, Davi Rodrigo [UNESP] (Elsevier, 2023)
Savannas in southeastern Brazil are frequently exposed to frost events, causing the death of leaves and branches in many woody and herbaceous species. Frost events are frequent in these regions, with one relatively stronger than usual event every 5 years. Our experimental site at São Paulo State, Southeastern Brazil, was affected by strong frost events during June–July 2021, when temperatures reached -4 °C, causing aboveground dieback in most ground layer species, although we observed some species were not affected and maintained a fully green canopy. We used this opportunistic frost event to study and report these damages and measured leaf traits that could explain our observations, as well as point directions to ecological understanding of frost on savanna vegetation. We measured morphological leaf traits such as leaf shape (width, length, width to length ratio), leaf area, specific leaf area and leaf thickness, and we also quantified canopy and leaf damage in 17 species (5 non-affected by frost and 12 that were visually affected). We found that species with larger and thicker leaves were more prone to leaf and canopy damage (70–100% of damage) than those with smaller and thinner leaves (0% damage). These results suggest that leaf morphology may provide resistance against frost and could ultimately act as a filter favoring species that can support extreme frost events, if those became more frequent and stronger under future climatic changes.
Keywords: Cerrado; Climate change; Disturbance; Frost resistance; Leaf morphology; Leaf traits